Inverse nodal problem with fractional order conformable type derivative - Sa'idu, Auwalu; Koyunbakan, Hikmet; Shah, Kamal; Abdeljawad, Thabet (Int Scientific Research Publications, 2024)
The present paper is about the inverse nodal problem for Sturm-Liouville problem with eigenparameter in the boundary condition using the conformable derivative approach. We defined a function f(mu) generally in the boundary condition and we found the zeros of the eigenfunctions (nodal points) by nucleus function K(x,t), which is a derived transformation operator. Then, we obtained the potential function by using the nodal parameters.
Keywords: Sturm Liouville problem; conformable derivative; nodal points; potential function; eigenparameter